COST-UTILITY ANALYSIS OVER USE OF TYROSINE KINASE INHIBITORS (TASIGNA AND GLEEVEC) FOR TREATMENT OF CHRONIC MYELOID LEUKEMIA IN THE CHRONIC PHASE AS FIRST-LINE THERAPY FOR DE NOVO PATIENTS - R. I. Yagudina; A. Yu. Kulikov; I. A. Komarov (Фармакоэкономика)
Chronic myeloid leukemia (CML) accounts for roughly 20% of leucosis in adults, and this pathology incidence is about 1-2 cases on 100 000 men annually. Pharmacoeconomic evaluation of this pathology contributes to the improvement of approaches to treatment policy of this group of patients. We performed cost-effectiveness analysis and cost-utility analysis on the basis of two tyrosine kinase inhibitors in Russian Federation – nilotinib (Tasigna) and imatinib (Gleevec) in CML in the chronic phase (CP) treatment as first-line therapy. Treatment with Tasigna compared with Gleevec characterizes as dominant or acceptable according to used time horizons.